Penerapan Media Power Point Untuk Peningkatan Hasil Belajar PAI Pada Siswa Kelas IV SD N 04 Muara Tais Tengah Kec. Mapat Tunggul Kab. Pasaman - Marlina, Sisra (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to enhance the quality of Islamic Education learning, particularly in the topic of Q.S. At-Tin, through the implementation of PowerPoint as a teaching medium. This classroom action research was conducted with fourth-grade students at SD N 04 Muara Tais Tengah using a cyclical approach comprising planning, implementation, observation, and reflection. The results show that in the first cycle, the overall learning mastery rate reached 71%, with 29% of students not meeting the minimum mastery criteria. Observations indicated that students’ learning activities still require improvement, particularly in active engagement aspects such as discussion, expressing opinions, and summarizing material. PowerPoint proved effective in enhancing material comprehension, but its use needs to be complemented with more interactive teaching strategies to achieve optimal outcomes.